Does Phillips Curve Exist? Empirical Evidence For Sabah And Sarawak - Yap, Li Yi (Universiti Malaysia Sarawak (UNIMAS), 2014)
The purpose of this study is to examine the causal relationship between inflation and unemployment by Phillips Curve in Sabah and Sarawak from 1982 to 2012. The econometrics methods of unit root tests, Johansen-Juselius cointegration test, and Granger causality test are applied in this study. The overall findings show that there is a significant Phillips Curve in the long run in Sabah and Sarawak. However, in the shortrun, the Phillips Curve is found to exist in Sarawak only.